KAJIAN SAINS PADA BENTUK BUMI UNTUK PENENTUAN ARAH KIBLAT - Reza Akbar; Ahmad Izzuddin (Al-Maslahah : Jurnal Ilmu Syariah, 2022)
Popper proposed a controversial notion of the truth of a theory that cannot be supported by observational evidence. According to him, it is impossible for a theory makes so many predictions that come true as expected. If his notion is associated with visual evidence of the Earth that has been recognized as a truth then the consequences are the photographs and everything related to the compatibility between the observations and the initial hypothesis comes to be questionable. Popper has the same view with Kuhn about the meaning of the truth of science that will not be final but rather a conjecture. Kuhn also proposed the stages of how science works. Based on the study on the progres of science of the Earth’s shape using the notions of Popper and Kuhn, it appears that the scientific progress of the Earth’s shape has experienced ideal stages. However, its progress has exceeded the scientific limit of science, as well as it still contains some ridiculousnesses of verificational evidence. This confirms that it is important for practitioners to use an appropriate paradigm because the truth of science can never be achieved as an actual truth. In the determination of the direction of Qibla, until now we know some methods namely calculation using the formula of spherical trigonometry, Vincenty’s formula, and global rashdul Qibla. Each method holds its own paradigm that has weaknesses and advantages. This research includes into qualitative research with library research approach. The author suggests to use rashdul qibla.